Implementing a Care Coordination Program for Children with Special Healthcare Needs: Partnering with Families and Providers. Issue 5 (22nd August 2012) - Taylor, April; Lizzi, Michele; Marx, Alison; Chilkatowsky, Maryann; Trachtenberg, Symme W.; Ogle, Sue
Abstract Care coordination has been a key theme in national forums on healthcare quality, design, and improvement. This article describes the characteristics of a care coordination program aimed at supporting families in building care coordination competencies and providers in the coordination of care across multiple specialties. The program included implementation of a Care Coordination Counselor (CC Counselor) and several supporting tools—Care Binders, Complex Scheduling, Community Resources for Families Database, and a Care Coordination Network. Patients were referred by a healthcare provider to receive services from the CC Counselor or to receive a Care Binder organizational tool. To assess the impact of the counselor role, we compared patient experience survey results from patients receiving CC Counselor services to those receiving only the Care Binder. Our analysis found that patients supported by the CC Counselor reported greater agreement with accessing care coordination resources and identifying a key point person for coordination. Seventy‐five percent of CC Counselor patients have graduated from the program. Our findings suggest that implementation of a CC Counselor role and supporting tools offers an integrative way to connect patients, families, and providers with services and resources to support coordinated, continuous care.